2017
DOI: 10.32404/rean.v4i4.1672
|View full text |Cite
|
Sign up to set email alerts
|

Influência De Fatores Ambientais, Cor E Altura De Armadilhas Na Captura Do Caruncho Do Bambu

Abstract: O objetivo deste trabalho foi avaliar o efeito da influência dos fatores ambientais, cor e altura de instalação de armadilhas com toletes de bambu na captura do Dinoderus minutus, considerado a principal praga pós-colheita do bambu. A literatura aponta a cor e altura das armadilhas como elementos capazes de influenciar na captura deste inseto. Para avaliar essas hipóteses, foram fabricadas 30 armadilhas de garrafas PET nas cores amarela, preta, branca, azul e transparente. Toletes de bambu Bambusa vulgaris for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…It is noteworthy that in research in the literature it was not possible to find works on survey of wood-boring beetles in general in Bambusa plantations in Brazil. Some punctual studies were observed with Dinoderus minutus, a pest species already known as in the work by Silveira et al (2017) who evaluated the influence of environmental factors, and color and height of traps in the capture of this pest species. Dinoderus minutus has already been recorded in the Alta Floresta region in Eucalyptus urograndis plantations (Monteiro et al, 2016), but it was not found in the collections carried out in this study.…”
Section: Methodological Proceduresmentioning
confidence: 99%
“…It is noteworthy that in research in the literature it was not possible to find works on survey of wood-boring beetles in general in Bambusa plantations in Brazil. Some punctual studies were observed with Dinoderus minutus, a pest species already known as in the work by Silveira et al (2017) who evaluated the influence of environmental factors, and color and height of traps in the capture of this pest species. Dinoderus minutus has already been recorded in the Alta Floresta region in Eucalyptus urograndis plantations (Monteiro et al, 2016), but it was not found in the collections carried out in this study.…”
Section: Methodological Proceduresmentioning
confidence: 99%
“…In this regard, due to its unequaled growth rate, bamboo yields more biomass and captures more atmospheric carbon per hectare than anything, thus removing more carbon from the sky and adding it to the soil. Although the usefulness of bamboo as an absorbent is not very well known, that which is cultivated in tropical and subtropical regions worldwide can be used as a renewable feedstock, as already occurs in many countries, especially in Asia (China, India, and Thailand), Central America (Costa Rica, Mexico, and Honduras), and South America (Peru, Ecuador, and Colombia) [99][100][101][102][103][104][105]. It has been reported that bamboo plantations can store four times more carbon than timber forests and that they are therefore considered as a potential alternative as a durable carbon stock [106].…”
Section: The Use Of Bamboo Biomass To Prepare Bc: a Plethora Of Advan...mentioning
confidence: 99%
“…The results indicate that it is in the rainy season the greatest activity of the bamboo borer. According to Silveira et al (2017b), the greatest presence of the borer corresponds to the days with higher temperatures and greater rainfall rates, where there is a natural occurrence of the insect D. minutus. The authors also observed a smaller number of insects captured in seasons with a lower relative air humidity, which is similar to the data obtained in the present study.…”
Section: Behavioral Assessment: Stage II -Laboratorymentioning
confidence: 99%